The Known Stranger: Supporting Conversations between Strangers with Personalized Topic Suggestions - Nguyen, Tien T.; Nguyen, Duyen T.; Iqbal, Shamsi; Ofek, Eyal (ACM Conference on Human Factors for Computing Systems (CHI), 2015)
Striking up a good conversation with new acquaintances is often difficult. In this paper we introduce a system that uses a ranking recommendation algorithm to generate real-time personalized topic suggestions during a conversation. The system then delivers the suggestions via Google Glass. We conducted a study with 38 pairs of strangers, who received such suggestions while conversing with a person they met for the first time. Participants found the suggestions to be helpful, but only at the right moments, and for certain types of speakers. Our results contribute to the understanding of how communication interventions influence people’s experience and behaviors, and enhance interpersonal interactions. Our study also presents design implications for applications on wearable devices to facilitate conversations between strangers.